Synthetic triterpenoid induces 15-PGDH expression and suppresses inflammation-driven colon carcinogenesis - Choi, Sung Hee (American Society for Clinical Investigation, 2014)
Colitis-associated colon cancer (CAC) develops as a result of inflammation-induced epithelial transformation, which occurs in response to inflammatory cytokine-dependent downregulation of 15-hydroxyprostaglandin dehydrogenase (15-PGDH) and subsequent suppression of prostaglandin metabolism. Agents that both enhance 15-PGDH expression and suppress cyclooxygenase-2 (COX-2) production may more effectively prevent CAC. Synthetic triterpenoids are a class of small molecules that suppress COX-2 as well as inflammatory cytokine signaling. Here, we found that administration of the synthetic triterpenoid 2-cyano-3,12-dioxooleana-1,9(11)-dien-C28-methyl ester (CDDO-Me) suppresses CAC in mice. In a spontaneous, inflammation-driven intestinal neoplasia model, deletion of Smad4 specifically in T cells led to progressive production of inflammatory cytokines, including TNF-α, IFN-γ, iNOS, IL-6, IL-1β; as well as activation of STAT1 and STAT3; along with suppression of 15-PGDH expression. Oral administration of CDDO-Me to mice with SMAD4-deficient T cells increased survival and suppressed intestinal epithelial neoplasia by decreasing production of inflammatory mediators and increasing expression of 15-PGDH. Induction of 15-PGDH by CDDO-Me was dose dependent in epithelial cells and was abrogated following treatment with TGF-β signaling inhibitors in vitro. Furthermore, CDDO-Me–dependent 15-PGDH induction was not observed in Smad3(–/–) mice. Similarly, CDDO-Me suppressed azoxymethane plus dextran sodium sulfate–induced carcinogenesis in wild-type animals, highlighting the potential of small molecules of the triterpenoid family as effective agents for the chemoprevention of CAC in humans.